2019
DOI: 10.1111/jonm.12857
|View full text |Cite
|
Sign up to set email alerts
|

The long‐term effects of psychological demands on chronic fatigue

Abstract: Aim Investigate the impact of psychological job demands and resources on chronic fatigue. Background Nurse fatigue is a serious problem with negative consequences on patient safety and nurse well‐being. Excessive job demands can exacerbate nurse fatigue, which may limit the ability of nurses to engage in professional practice. Methods This two‐wave study was carried out with a self‐report questionnaire administered to nurses in eastern Canada (n = 154). Cross‐lagged analysis using structural equation modelling… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 41 publications
1
13
0
Order By: Relevance
“…Finally, the present study adds to the existing literature on the most relevant psychosocial factors peculiar to healthcare professionals' (and particularly, nurses') health and wellbeing (for reviews, see [33,34]). For instance, our results are in line with previous studies highlighting the relationship between nurses' wellbeing (e.g., emotional exhaustion, chronic fatigue, psychosomatic complaints) and both cognitive [54][55][56] and emotional job demands [57], work-family conflicts [37,39,54], and excessively demanding, difficult or hostile patients [54,58]. Patient-related social stressors have been highlighted among the most relevant factors to be considered when examining nurses' wellbeing (see [59]), with emotional exhaustion being found predicted by perceived hostility from patients [54], verbal abuse from both patients and visitors [60], and by the frequency of interactions with difficult patients [58].…”
Section: Discussionsupporting
confidence: 93%
“…Finally, the present study adds to the existing literature on the most relevant psychosocial factors peculiar to healthcare professionals' (and particularly, nurses') health and wellbeing (for reviews, see [33,34]). For instance, our results are in line with previous studies highlighting the relationship between nurses' wellbeing (e.g., emotional exhaustion, chronic fatigue, psychosomatic complaints) and both cognitive [54][55][56] and emotional job demands [57], work-family conflicts [37,39,54], and excessively demanding, difficult or hostile patients [54,58]. Patient-related social stressors have been highlighted among the most relevant factors to be considered when examining nurses' wellbeing (see [59]), with emotional exhaustion being found predicted by perceived hostility from patients [54], verbal abuse from both patients and visitors [60], and by the frequency of interactions with difficult patients [58].…”
Section: Discussionsupporting
confidence: 93%
“…It has also been found in Iceland that job stressors play a role in nurses' excess risk of suicide (Gunnarsdottir & Rafnsson, 1995). Others have found that job stressors and decision latitude (over-regulation and loss of autonomy) have long-lasting negative effects on the psychological health of nurses (LeGal, Rheaume, & Mullen, 2019). Nurses were more likely to have received mental health care, implying that access to health care may not be a primary risk.…”
Section: Workplace Wellness: Prevention and Risk Detectionmentioning
confidence: 99%
“…Our study points to two factors amenable to interventions that may be overlooked: the chronic occupational fatigue suffered by many nurses, including those in leadership, and nurses' meaning and joy in work. A recent study of Canadian nurses (LeGal et al., 2019) found that while psychological job demands predicted chronic fatigue a year later, job resources (decision latitude, social support) did not attenuate the relationship between these demands and chronic fatigue.…”
Section: Discussionmentioning
confidence: 98%
“…(2006) reported a significant mediating role of inter‐shift recovery between the relationship of acute and chronic fatigue indicating that poor inter‐shift recovery and high acute fatigue facilitated chronic fatigue. In nurses, chronic fatigue is related to cumulative hours worked (Barker & Nussbaum, 2011; Caldwell et al., 2019; Fang et al., 2013), psychological demands (LeGal et al., 2019; Winwood et al., 2006), low job satisfaction (Fang et al., 2013; Han et al., 2014), lower sense of meaning at work and inadequate social support (Han et al., 2014).…”
Section: Introductionmentioning
confidence: 99%